The intricacy of languages - Feliu, Francesc; Fullana, Olga (IVITRA research in linguistics and literature ;, 2019)
"If, as we believe, the history of languages is the history of the construction of an ideal artefact that permits a specific interpretation of the linguistic reality and helps to approve and assimilate a certain zone of diversity, enabling the accumulation of collective historical knowledge and making us identify it with a social community and a territory, then it must be agreed that languages are extremely complex entities. The new linguistic diversity that cultural globalisation and recent population movements have installed in most traditional linguistic territories has probably put the ideology of the national language into a state of crisis and, as a consequence, has made the ancient, intrinsic diversity of all languages visible, at least to the extent that this is still possible. Nowadays, then, the old linguistic diversity of dialects, of parlances, of local lexicons and the cultural forms that are reflected in these, of varieties and previously unsuccessful linguistic entities has been given a new opportunity in a world where the cohesion of societies and the welfare of citizens must be guaranteed using all available means. Looked at this way, the intricacy of languages may even open up an opportunity for local economic and social development"--